Penggunaan Limbah Pertanian Tanaman Pangan Sebagai Pakan Ternak Kerbau pada Peternak di Kecamatan Moa Maluku Barat Daya - Patty, Christian W; Sangadji, Insun (Jurnal Agrosilvopasture-Tech, 2025)
This study aims to identify the types of available agricultural waste, evaluate its use as feed for buffalo livestock, and assess the level of knowledge among farmers regarding the processing techniques of such waste. The approach used in this research is a combined research method with direct field observations. Sampling was conducted through purposive sampling, selecting three villages with the highest population of farmer-breeders: Werwaru Village, Klis Village, and Tounwawan Village. A total of 30 breeders were made respondents in this study. The results showed that most breeders (80%) raised buffalo as a form of savings, while the remaining (20%) viewed it as a side business. The composition of the forage feed used consists of 80% grass and 20% agricultural waste. The utilization rate of agricultural waste from food crops as feed for ruminant livestock is still relatively low, at 23.33%. Farmers who utilize agricultural waste, particularly corn stover in the form of hay (dried straw), only use it as additional feed. All respondents (100%) lack knowledge and skills in the application of waste-based feed processing technology. In general, the low use of agricultural waste as feed for buffaloes in Moa Island, Southwest Maluku Regency, is due to a lack of understanding and minimal application of feed processing technology by farmers and breeders in the region.